The Study of Potential Medicinal Plants of Ampara District (Karaitivu) and the Conservations in the Vicinity of Their Habitats - Sathiyaseelan, V.; Koneaswaran, K. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2016)
Medicinal plants used in herbalism have medicinal activities, nutritional values and recommended for their therapeutic values. The objective of the study is to determine the medicinal plants of Ampara district Karaitivu, Ampara. A Tropical coastal area contains rarely found plants in other areas. A survey study has been carried out for three months (May-July 2016) in some abandoned lands, places rich with medicinal plants through field trips and made conversation with old generation people connected with them. Total of 152 medicinal plant species belonging to 56 families were identified. This comprises perennials (59.86%), annuals (36.18%) and biennials (3.94%). Based on morphology herbs (25%), trees (33.55%), shrubs (21.71%), climbers (15.13%), cactus (0%), aquatic medicinal plants (4.60%). Based on their action, non poisonous plant (94.07%), poisonous plant (5.92%). According to the parts use of medicine whole plants (24.14%), leaves (27.68%), barks (10.33%), flowers (4.30%), roots (15.70%), seeds (6.19%), fruits (7.43%), rhizomes (3.71%) and woods (2.47%). Considering with disease Diabetes Mellitus (7.10%), skin diseases (16.44%), respiratory diseases (13.15%), and traditional practitioners using for fracture treatment (8.55%) are used in medicinal purposes. Among these medicinal plants (17) are proportionately found higher in the coastal area than other climatic zones of Sri Lanka. Some of these comprise Launaea pinnatifolia, Glinus lotoides, Bambusa arundinaceae and Pandanus tectorious. The "Manpanchan" is a plant (unbotanical named) but traditional practitioner's use this plant for Diabetic Mellitus & also wound healing condition. Its synonym is "Mathuviratti". Epiphytes (2), plants used as substitutes for genuine plants (3), misidentified plants (5) and (90-100) are used by Siddha and Ayurvedic traditional medicine practitioners. Though Ampara is a wet zone it contains Costal area plants, Aquatic plants and Mangrooves too. Such are P. tectorius, Pisticia stratiotes, Oryza sativa and Nymphaea stellata. The conservation achieved through in-situ and ex-situ to promote the sustainable use via socio awareness education.
Keywords: Ampara district; Medicinal plants; Conservation